Theoretical Principles of Sociology, Volume 3 - Turner, Jonathan H. author. aut Link
XIV, 434 p.
Keywords: The meso-level realm of social reality is structured by corporate and categoric units, along with their respective cultures. Unlike the macro and micro realms of social reality, the meso-level does not reveal its own unique forces. Rather, the dynamics of meso-structures and cultures are driven by macro- and micro-level forces pushing on individual and collective actors as they build corporate units and develop parameters defining membership in particular social categories.